Scrum-Based Mobile Application Development for Patient Satisfaction Assessment in Class 'B' Hospitals in Padang - Nabilla, Regina; Dian, Yulef; Idris, Iswandi (AI Society & STMIK Indonesia, 2024)
The assessment of patient satisfaction is a critical aspect of healthcare services, providing valuable insights into the quality of care and service delivery. In Padang's Class